Role of Non-coding Regulatory RNA in the Virulence of Human Pathogenic Vibrios - Pérez-Reytor, Diliana; Plaza, Nicolás; Espejo, Romilio T.; Navarrete, Paola; Bastías, Roberto; Garcia, Katherine (Frontiers in Microbiology, 2017)
In recent decades, the identification of small noncoding RNAs in bacteria has revealed an important regulatory mechanism of gene expression involved in the response to environmental signals and to the control of virulence. In the family Vibrionaceae, which includes several human and animal pathogens, sRNAs are closely related to important processes including metabolism, quorum sensing, virulence and fitness. Studies conducted in silico and experiments using microarrays and high-throughput RNA sequencing have led to the discovery of an unexpected number of sRNAs in Vibrios. The present review discusses the most relevant reports regarding the mechanisms of action of sRNAs and their implications in the virulence of the main human pathogens in the family Vibrionaceae: Vibrio parahaemolyticus, V. vulnificus and V. cholerae.